2020
DOI: 10.1002/oby.23076
|View full text |Cite
|
Sign up to set email alerts
|

BMI as a Risk Factor for Clinical Outcomes in Patients Hospitalized with COVID‐19 in New York

Abstract: Objective This study examined the association between BMI and clinical outcomes among patients with coronavirus disease 2019 (COVID‐19) infection. Methods A total of 10,861 patients with COVID‐19 infection who were admitted to the Northwell Health system hospitals between March 1, 2020, and April 27, 2020, were included in this study. BMI was classified as underweight, normal weight, overweight, and obesity classes I, II, and III. Primary outcomes were invasive mechanical ventilation (IMV) and death. Results A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 17 publications
(17 reference statements)
10
65
0
8
Order By: Relevance
“…To account for potential confounders, especially the age difference, we created a multivariate model where we adjusted for the effect of age, body mass index (BMI), gender, race, diabetes, HTN, chronic lung disease and heart disease on outcomes. Consistent with published literature( 49-52 ) (age and BMI were positively associated with COVID-19 severity and mortality (table S9. Using this multivariate model, we analyzed the impact of GI symptoms on disease outcomes.…”
Section: Resultssupporting
confidence: 90%
“…To account for potential confounders, especially the age difference, we created a multivariate model where we adjusted for the effect of age, body mass index (BMI), gender, race, diabetes, HTN, chronic lung disease and heart disease on outcomes. Consistent with published literature( 49-52 ) (age and BMI were positively associated with COVID-19 severity and mortality (table S9. Using this multivariate model, we analyzed the impact of GI symptoms on disease outcomes.…”
Section: Resultssupporting
confidence: 90%
“…Meanwhile, Santos et al reported that dyslipidemia as an independent predictor of mortality 19 . Obesity and chronic liver disease, including fatty liver disease, may affect the association between dyslipidemia and poor outcome; because both obesity and fatty liver disease are associated with poor prognosis 24 , 25 , 26 . However, meta-regression analysis was not possible because only three studies were reporting chronic liver disease, and one study reporting obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Estas dos características, la edad mayor a 60 años y el sexo masculino, fueron también factores de riesgo asociados con necesidad de VM en nuestra población. Muchos estudios observaron que los pacientes con obesidad (IMC>30 kg/m 2 ) tenían más probabilidades de cursar cuadros graves (15,16). Sin embargo, en nuestra población, si bien más de la mitad de los pacientes eran obesos, esta condición no constituyó un factor independiente predictor de necesidad de VM.…”
Section: Resultsunclassified